Lavish returns on cheap talk: Non-binding communication in a trust experiment - Avner Ben-Ner; Louis Putterman; Ting Ren (Brown University, Department of Economics, 2007)
We let subjects interact with anonymous partners in trust (investment) games with and without one of two kinds of pre-play communication: numerical (tabular) only, and verbal and numerical. We find that either kind of pre-play communication increases trusting, trustworthiness, or both, in inter-subject comparisons, but that the inclusions of verbal communication generates both a larger effect and one that is robust across both inter-subject and intra-subject comparisons. In all conditions, trustors earn more when they invest more of their endowment, trustors and trustees gravitate to fair and efficient interactions, and the majority of trustees adhere to their commitments, whether explicit or implicit. Finally, we study trusting and trustworthiness in the sense of adhering to agreements, and we find that both are enhanced when the parties can use words, and especially when an agreement is reached with words and not only with the exchange of numerical proposals.
Keywords: C72; C91; D63; 330; trust game; trust; trustworthiness; reciprocity; commitment; communication; cheap talk; Nichtkooperatives Spiel; Vertrauen; Kommunikation; Theorie